New metal/superconductor-insulator transitions and their effects on high-tc superconductivity in underdoped and optimally doped cuprates - Kurbanov, U.T.; Zhumabaeva, G.K.; Dzhumanov, S. (Karagandy University of the name of acad. E.A. Buketov, 2024)
A new approach to the metal/superconductor-insulator transition in doped cuprates by studying the polaron formation and localization of doped charge carriers (holes) in them and the possibility of transforming a metallic or superconducting system into an insulator was developed. A more suitable criterion for such a phase transition by comparing the bandwidth (or Fermi energy) of large polarons with their binding energies in the cuprates was derived. The possibility of the metal/superconductor-insulator transition and phase separation in doped cuprates resulting in the formation of competing metallic/superconducting and insulating phases in underdoped, optimally doped and even in overdoped high-Tc cuprates was predicted. Then the possible detrimental and beneficial effects of the different disorders (e.g. polaron formation and charge-density-wave transition) and the coexisting insulating and superconducting phases on the critical temperature `a of the superconducting transition of underdoped and optimally doped cuprates was examined. The actual superconducting transition temperature `a in these materials using the theory of Bose-liquid superconductivity, and not the Bardeen-Cooper-Schrieffer-like theory of Fermi-liquid superconductivity, which is incapable of predicting the relevant value of `a in high-`a cuprates was determined. We find that the suppressing of the polaronic and charge-density-wave effects in optimally doped cuprates results in the enhancement of `a, while some lattice defects (e.g., anion vacancies) in the cuprates may strongly affect, on `a and enhance high-`a superconductivity in them.
Keywords: polaron formation and charge density waves; metal/superconductor-insulator transition; cuprates; Bose-liquid superconductivity; different disorders; suppression and enhancement of high-`a superconductivity